Transmisi Pengetahuan Pembuatan Bedog Cikeruh pada Lembaga Informal Dangiang Pusaka Domas di Tanjung Sari Sumedang - Muhammad Rizki Syamsudin; Sukaesih Sukaesih; Yunus Winoto (Universitas Galuh, 2023)
Bedog Cikeruh is a cultural heritage originating from Jatinangor District, Sumedang Regency (formerly Jatinangor named Cikeruh). At this time the knowledge of making Bedog Cikeruh is in a critical state. The author found that in the area around Jatinangor, there is only one blacksmith who is still actively producing Bedog Cikeruh. The organization is called Dangiang Pusaka Domas. Dangiang Pusaka Domas is an informal family-based organization. Dangiang Pusaka Domas blacksmith is located in Maruyung Hamlet, Kutamandiri Village, Tanjungsari District, Sumedang Regency. Through this article, the author intends to present data from the point of view of Knowledge Management, how knowledge is shared through knowledge transmission in the Dangiang Pusaka Domas Blacksmith based on the following research questions: (1) What is knowledge transmission? (2) How does the knowledge transmission process take place in the Dangiang Pusaka Domas blacksmith? To obtain the necessary data, the author collected data by conducting an in-depth interview of the source of information obtained based on purposive sampling techniques. The author's findings show that: knowledge transmission is part of the knowledge sharing process. This concept refers to social interaction in which there is a transfer of knowledge, experience, and skills from one individual to another. Furthermore, some conclusions about the transmission of knowledge in the context of Dangiang Pusaka Domas, as an informal organization are: (1) The process of knowledge transmission, in this case, blacksmith knowledge, is carried out for generations in families vertically. (2) The process of knowledge transmission is carried out through structured participation and guidance. (3) The selection of individuals to pass on knowledge is generally in the family lineage, but the decline in knowledge focuses more on internal motivations and personal empirical experience. (4) The process of transmitting knowledge does not involve documenting or converting tacit knowledge into explicit knowledge. Knowledge is passed down through direct experience and practice, without written record-keeping. (5) The family is open to receiving individuals from outside the family who wish to learn blacksmithing knowledge.